Characterizing of “Urban Heat Island” phenomenon in central zone of city of guayaquil - Palacios Portés, Carlos (Revista Universidad de Guayaquil, 2013)
This paper deals with the determination of the physical conditions that cause the urban heat island phenomenon in the central zone of the city of Guayaquil, a place of which actual appearance has been replicated in every local process of urban regeneration. In order to achieve this, it was necessary to take in-situ thermal profiles of twenty three street intersections along a study transect, with the quantification of thermal masses in accordance with coverage materials and their underlying layers one foot depth down the finished floor elevation; besides worked with the estimated anthropogenic heat production after evaluate the built intensity and land use in the study zone, finally calculated sky view factors caused by buildings, vegetation and topography in general. With the results, the numeric model will be a starting point for future urban climate investigations that are intended to predict the effects of replication of these covers in other urban zones with similar urban geometry.
Keywords: urban heat island; anthropogenic heat; urban covers; urban geometry; building thermal mass